A POD Modulation Technique Based Transformer less HERIC Topology for PV Grid Tied-Inverter - Nireekshana Namburi (E3S Web of Conferences)
Transformer-based inverters offer galvanic isolation, which improves safety by physically disconnecting the PV array from the grid. Simultaneously, transformers contribute to extra energy losses as a result of their intrinsic resistance and inductance, resulting in reduced overall system efficiency. Integrating a transformer within the inverter increases its size and weight, which adds complexity to the installation process and necessitates stronger mounting options. Transformers produce excess heat, which requires more advanced cooling methods and may decrease the lifespan of the inverter components owing to thermal strain. Transformers can restrict the inverter’s frequency response, which can impact its capacity to rapidly adjust to variations in load or grid circumstances. Hence, in order to circumvent these intricacies, this article introduces a transformer less full-bridge PV grid structure. The proposed technique is an advanced and efficient technology that con-verts DC voltage generated by photovoltaic (PV) solar panels into AC voltage that can be safely fed into the electrical grid. This inverter employs a HERIC topology. HERIC transformer-less full-bridge PV grid-tied inverters are an advanced and efficient option for converting solar power into electricity. They are very dependable and are ideal for cur-rent PV systems that focus on maximum energy production while reducing installation and operational expenses. This article presents the development of a HERIC transformer-less photovoltaic (PV) grid-tied inverter using insulated-gate bipolar transistor (IGBT) switches in MATLAB Simulink.